Solid‐State NMR and DFT Studies on the Formation of Well‐Defined Silica‐Supported Tantallaaziridines: From Synthesis to Catalytic Application. Issue 9 (27th January 2016) - Hamzaoui, Bilel; Pelletier, Jérémie D. A.; Abou‐Hamad, Edy; Chen, Yin; El Eter, Mohamed; Chermak, Edrisse; Cavallo, Luigi; Basset, Jean‐Marie
Abstract: Single‐site, well‐defined, silica‐supported tantallaaziridine intermediates [≡Si‐O‐Ta(η 2 ‐NRCH2 )(NMe2 )2 ] [R=Me (2 ), Ph (3 )] were prepared from silica‐supported tetrakis(dimethylamido)tantalum [≡Si‐O‐Ta(NMe2 )4 ] (1 ) and fully characterized by FTIR spectroscopy, elemental analysis, and 1 H, 13 C HETCOR and DQ TQ solid‐state (SS) NMR spectroscopy. The formation mechanism, by β‐H abstraction, was investigated by SS NMR spectroscopy and supported by DFT calculations. The C−H activation of the dimethylamide ligand is favored for R=Ph. The results from catalytic testing in the hydroaminoalkylation of alkenes were consistent with the N ‐alkyl aryl amine substrates being more efficient than N ‐dialkyl amines. Abstract : Single‐site well‐defined silica‐supported tantallaaziridines [≡Si‐O‐Ta(η 2 ‐NRCH2 )(NMe2 )2 ] (R=Me, Ph) were isolated and fully characterized. The formation mechanism by β‐H abstraction was investigated by solid‐state NMR spectroscopy and supported by DFT calculations. Catalytic testing for the hydroaminoalkylations of alkenes were consistent with the N ‐alkyl‐arylamine substrates being more efficient than N ‐dialkylamines (see scheme).